PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP KEUNGGULAN KOMPETITIF DAN KINERJA PERUSAHAAN PADA UMKM INDUSTRI KULINER DI JAKARTA BARAT - Derani Syahreva; Lutfi Alhazami (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
This study aims to determine the effect of supply chain management on competitive advantage and company performance in the culinary industry SMEs in West Jakarta. This study uses a quantitative approach with the subject of this research is the culinary industry SMEs in West Jakarta. The number of samples is 92 and the instrument used is a questionnaire. Instrument quality testing includes validity and reliability tests using IBM SPSS 26. The data analysis method uses path analysis. The results show that supply chain management affects company performance, supply chain management affects competitive advantage, superiority Competitive advantage affects the company's performance, and supply chain management affects the company's performance through or without competitive advantage. However, it tends to have a direct effect on company performance. This analysis was only conducted in the West Jakarta area and this study only examined the supply chain management, competitive advantage. So there are other variables that affect the company's performance that are not included in this study.